A natural antisense transcript acts as a negative regulator for the maize drought stress response gene ZmNAC48. (22nd January 2021) - Mao, Yan; Xu, Jie; Wang, Qi; Li, Guobang; Tang, Xin; Liu, Tianhong; Feng, Xuanjun; Wu, Fengkai; Li, Menglu; Xie, Wubing; Lu, Yanli
Abstract: Although plant-specific NAC transcription factors play crucial roles in response to abiotic stress, few reports describe the regulation of NAC genes in maize ( Zea mays ) by the cis -natural antisense transcripts ( cis -NATs). In this study, 521 NAC genes from Gramineae were classified, of which 51 NAC genes contained cis -NATs. ZmNAC48 and cis- NAT ZmNAC48 co-localized to the same cell nucleus, and both transcripts responded to drought stress. Arabidopsis plants overexpressing ZmNAC 48 had improved drought tolerance, lower rate of water loss, enhanced stomatal closure, and higher rates of survival. Transient expression in both maize protoplasts and tobacco leaves indicated that cis- NAT ZmNAC48 reduced ZmNAC48 expression. Western blotting and ribosome profiling analyses confirmed that cis -NAT ZmNAC48 lacked protein coding potential. Furthermore, the cis -NAT-derived small-interfering RNAs (nat-siRNAs) generated from the overlapping regions of ZmNAC48 and cis- NAT ZmNAC48 were detected in maize and transgenic Arabidopsis. Cis -NAT ZmNAC48 overexpressing maize showed higher water loss rate, increased stomatal opening, and had more dead leaves. Expression of ZmNAC48 and nat-siRNA was decreased in these plants. Taken together, our study indicates that both ZmNAC48 and cis -NAT ZmNAC48 are involved in plant drought stress responses, and that the double-stranded RNA-dependent mechanism is involved in the interaction between cis -NAT ZmNAC48 and ZmNAC48 . Additionally, cis -NAT ZmNAC48 may negatively regulate ZmNAC48 to affect stomatal closure of maize. Abstract : Cis -NAT ZmNAC48, a negative regulator for the maize drought stress response gene ZmNAC48, regulates stomatal closure in maize.